Hailey-Hailey disease successfully treated with naloxone: 2 case reports and Review of the literature on efficacy of opioid receptor antagonist in Hailey-Hailey disease patients - Junyou Zheng; Zhimin Duan; Beilei Xu; Hao Song; Jianbing Wu; Fang Fang; Nan Sheng; Chengrang Li (Journal of Dermatological Treatment)
Background Hailey–Hailey disease (HHD), a genetic blistering disease, is caused by a mutation in a calcium transporter protein in the Golgi apparatus encoded by the ATP2C1 gene. Clinically, HHD is characterized by flaccid vesicles, blisters, erosions, fissures, and maceration mainly in intertriginous regions. Some patients remain refractory to conventional treatments. Previously, a series of reports have confirmed naltrexone as an effective option for those patients. However, in China, naltrexone is unavailable in some hospitals and unaffordable for some patients.Objective To confirm naloxone as a treatment option for HHD, and assess the efficacy rate and safety of naltrexone for patients with HHD.Methods Two patients with biopsy-proven HHD received naloxone (2 mg/d, via intravenous infusion). We followed up with the two patients, assessing the change of skin lesions and obtaining photographs. We searched the PubMed databases using the keywords ‘Hailey-Hailey disease’ or ‘benign familial pemphigus’, and ‘naltrexone’ or ‘naloxone’, and reviewed English publications of reports and analyzed the efficacy and safety of naltrexone.Results Two patients prescribed naloxone showed completely remission in two weeks without any adverse reactions. The total remission rate of naltrexone for HHD is approximately 80%, without severe adverse effects.Conclusion Naltrexone is effective and safe in the treatment of HHD. Naloxone, an analog of naltrexone, can also effectively and safely treat HHD, potentially offering a new therapeutic option for patients with refractory HHD.